Targeting 1.5 degrees with the global carbon footprint of the Australian Capital Territory. Issue 144 (June 2023) - Goodwin, Kylie; Allen, Cameron; Teh, Soo Huey; Li, Mengyu; Fry, Jacob; Lenzen, Manfred; Farrelly, Serena; Leon, Constanza; Lewis, Sophie; Chen, Guangwu; Schandl, Heinz; Wiedmann, Thomas
Abstract: In 2019 the Australian Capital Territory (ACT) government stated an ambition to prioritise reduction of Scope 3 greenhouse gas emissions, the size of which had not been fully quantified previously. This study calculated the total carbon footprint of the ACT in 2018, including Scope 1, 2 and 3 emissions and modelled scenarios to reduce all emissions in line with a 1.5 °C target approach. This is the first time a multi-scale analysis of local, sub-national and international supply chains has been undertaken for a city, using a nested and trade-adjusted global multi-region input-output model. This allowed for the quantification of global origins and destinations of emissions, which showed that the 2018 carbon footprint for the ACT was approximately 34.7 t CO2 -eq/cap, with 83% attributed to Scope 3. Main contributions came from transport, electricity, manufacturing and public administration and safety, with emissions generated primarily in Australian States and Territories. Modelling in accordance with a 1.5 °C warming scenario showed a plausible reduction to 5.2 t CO2 -eq/cap by 2045 (excluding offsets or carbon dioxide removal technologies), with remaining emissions predominantly embodied in international supply chains. This study demonstrates the radical changes required by a wealthy Australian city to achieve 1.5 °C compliance and identifies sectors and supply chains for prioritising policies to best achieve this outcome. Highlights: Co-production of policy-focused research between government and academia. Fully nested, multi-scale, local-to-international supply chain analysis of a city. 83% of consumption-based emissions in 2018 were Scope 3. Modelled scenarios show a rapid decline in per-capita carbon footprint to 2045. Identifies highest-emitting sectors and regions at both final demand and source level.